Comparative Analysis of the Trade Relations of Argentina-Indonesia and Chile-Indonesia:: Their Similarities and Differences. What Can You Learn from the Neighboring Country? - Sterzer, Sebastian; Pakkanna, Andi Killang (Latin American Journal of Trade Policy, 2020)
Chile and Argentina have put their radars on trade with Southeast Asian countries, in which Indonesia appears as one of the main countries. In recent years, Chile has had a more aggressive trade policy towards Indonesia. The most recent proof has been the signing of the Indonesia - Chile Comprehensive Economic Partnership Agreement (IC-CEPA), which entered into force in 2019. The objective of this article is to present a comparative analysis of trade flows between Argentina - Indonesia and Chile - Indonesia, looking for similarities and differences between both types of bilateral ties, so that they can serve as models to improve existing relations, learning from what it has happened in each one of them.